Da barra ao findar do dia: hipermodernidade no cotidiano de pessoas idosas - Maria Cleonice Mendes de Souza (2013)
The current project aims to investigate how people over seventy years old live with the modernity and what is the influence of this phenomenon in their personalities / identities, in a historical moment which beholds the eight past decades from the twentieth century and the first decade in the twenty-first century. This research has as a preferential study locus three different geographical points in the state of Minas Gerais: first, the city of Montes Claros, located in the northern region which, by gathering 400 thousand inhabitants , presents characteristics of a medium size city, or a small capital; the second point, the city of Diamantina, nation-wide known and the bearer of traditional historic references, inhabited, nowadays, by 50 thousand people and, finally, the district of Itamirim, with obvious rural characteristics, still part of the city of Espinosa, bordering the state of Bahia and presenting a population over 700 inhabitants. The subjects, are people who were born between 1916 and 1940, ranging today, 2013, from 73 to 97 years old. In order to make the adequate questions to this project answered, it was necessary for these people to give away their memories so that the present time could be analyzed according to the memories of other times. For its project´s own nature, this researcher adopted the qualitative research methodology, emphasizing the oral communication tools. Authors as Halbwachs, that have showed studies in the memory field, besides Lipovetsky and Bauman, modern age searchers and study enthusiasts, constitute the main bibliographic reference in this research, as well as Bosi, elder people memories specialist, without forgetting Thompson and others linked to the oral section of History, those who were extremely important for this work. The results confirm, partly, some of the hypothesis considered for the project. Concerning the technology use, exclusively personal computer, only three from the twelve interviewed said they use this tool and, even though, with the exclusive purpose of work; the mobile phone technology was other of the technologies the interviewed said they rarely use and six of them said they have never had one. The interviewed, unanimously, affirm they have a good relationship with their children and grandchildren, blaming on technology advances, however, some attitudes that the younger ones present nowadays. According to the interviewed, there is no longer the commitment among people, inside the patterns that were conceived in the past decades. Besides criticizing modern punctual aspects, the interviewed, on the other hand, point out some considerable advantages, among them, how easy life has become due to the technology, with special attention to the appliances that have made household life more pleasant, less tiring and a lot more comfortable; they also credit the medicine advances that provide to a significant part of the population higher life expectancy and a better life quality, free from diseases. The interviewed see the consumption as a negative factor that harmfully interferes in the personal and social relations, since it does not attain to the superfluous and the excess of objects offered to people, extending to other maladies, visible in the human behavior. None of the interviewed confess themselves as nostalgic. It is noticeable, nevertheless, in their reports, some fond feelings towards old times, specially the youth and infant bliss. The inhabitants of the rural village of Itamirim who participated in this search, curiously, show a strong appreciation to the modernity, an understandable fact when realizing that this very same modernity, in the past five decades, that brought them the luxury of electricity, and the comforts of a less sacrificed life.